Diretrizes curriculares para o ensino de história e cultura afro-brasileira e indígena: implementação e impactos na formação, saberes e práticas de professores de história iniciantes (Mato Grosso, Brasil ) - Cerezer, Osvaldo Mariotto (2015)
This Thesis is resulting of a research that had as objective to analyze the implementation of the Laws No. 10.639/03 and 11.645/08 and the respective curricular Guidelines in degrees courses in History of three public universities in Mato Grosso State, Brazil (UNEMAT, UFMT and UFMT Rondonópolis Campus) and the impacts on the initial formation of History teachers and in the teaching of these thematics in public and private schools. The theoretical and methodological referential inspire on critical multiculturalism and qualitative approach, combining the analysis of oral and documentary sources (laws, guidelines, curricula and other) and in the bibliographic production about the theme. The subjects of the research were eleven History teachers egress from the three courses studied, in the initial phase of the teaching profession, and seven former professors from the respective Courses. To accomplish the oral interviews, transcribed and textualized posteriorly, we adopted the procedures of the thematic oral history. The thesis is organized in five Chapters, plus the Introduction and Final Considerations. In the first chapter presents the \"Scenery of the research: Mato Grosso a territory in multicultural disputes\", focalizing the historical formation of the Mato Grosso State, the conflicting relations among indigenous communities, not indigenous and African slaves, configuring a multiethnic and multicultural territory, and some of the current issues about the theme. The second chapter \"International and national political actions to combat racism, discrimination, xenophobia and correlate actions\" addresses the international and national political actions to combat racism, racial discrimination and correlate actions, with emphasis to the education of the ethnic-racial relations and the study of African, Afro-Brazilian and indigenous history and culture in Brazil. In the third chapter \"African, Afro-Brazilian and indigenous history and culture in college course of History in public higher education institution (IES) of Mato Grosso\" presents an analysis of the initial formation in History courses related to the implementation of the study of African, Afro-Brazilian and indigenous history and culture in initial formation and the impacts on knowledges and teaching practices. The chapter IV \"Among knowledges and practices of beginner history teachers: the study of Afro-Brazilian and indigenous thematics in basic education\", exposes a register and reflection about the narratives of the investigated beginner teachers, about the implementation and impacts on Basic Education in Mato Grosso State. The chapter V \"The study of Afro-Brazilian and indigenous thematic in Mato Grosso State dialogues\" offers an analysis of the dialogues between the documentation and the narratives produced via oral interviews with Former Professors and Beginner Teachers formed in History courses from public universities of Mato Grosso State. The \"Final Considerations\" of the Thesis bring a final analysis of the central problematic of the research and the results obtained. Thus, the study aims to contribute to the debate about the formation of History teachers and the relations with the knowledges and pedagogical practices in the teaching of African, Afro-Brazilian and indigenous history and culture in the current Brazilian educational context.